Characterization of hepatitis C virus intergenotypic recombinant strains and associated virological response to sofosbuvir/ribavirin. Issue 2 (15th December 2014) - Hedskog, Charlotte; Doehle, Brian; Chodavarapu, Krishna; Gontcharova, Viktoria; Crespo Garcia, Javier; De Knegt, Robert; Drenth, Joost P.H; McHutchison, John G.; Brainard, Diana; Stamm, Luisa M.; Miller, Michael D.; Svarovskaia, Evguenia; et al.
<x xml:space="preserve">Abstract</x> To date, intergenotypic recombinant hepatitis C viruses (HCVs) and their treatment outcomes have not been well characterized. This study characterized 12 novel HCV recombinant strains and their response to sofosbuvir in combination with ribavirin (SOF/RBV) treatment. Across the phase II/III studies of SOF, HCV samples were genotyped using both the Siemens VERSANT HCV Genotype INNO‐LiPA 2.0 Assay (Innogenetics, Ghent, Belgium) and nonstructural (NS)5B sequencing. Among these patient samples, genotype assignment discordance between the two methods was found in 0.5% of all cases (12 of 2, 363), of which all were identified as genotype 2 by INNO‐LiPA (12 of 487; 2.5%). HCV full‐genome sequences were obtained for these 12 samples by a sequence‐independent amplification method coupled with next‐generation sequencing. HCV full‐genome sequencing revealed that these viruses were recombinant HCV strains, with the 5' part corresponding to genotype 2 and the 3' part corresponding to genotype 1. The recombination breakpoint between genotypes 2 and 1 was consistently located within 80 amino acids of the NS2/NS3 junction. Interestingly, one of the recombinant viruses had a 34‐amino‐acid duplication at the location of the recombination breakpoint. Eleven of these twelve patients were treated with a regimen for genotype 2 HCV infection, but responded as if they had genotype 1 infection; 1 patient had received placebo. Conclusion: Twelve new HCV intergenotypic recombinant genotype 2/1 viruses have been characterized. The antiviral response to a 12‐ to 16‐week course of SOF/RBV treatment in these patients was more similar to responses among genotype 1 patients than genotype 2 patients, consistent with their genotype 1 NS5B gene (Hepatology 2015;61:471‐480)